Effect of Puerarin Regulated mTOR Signaling Pathway in Experimental Liver Injury - Bu-Gao Zhou; Hai-Mei Zhao; Xiu-Yun Lu; Wen Zhou; Fu-Chun Liu; Xue-Ke Liu; Duan-Yong Liu; Duan-Yong Liu (Frontiers Media S.A., 2018)
It is known that excessive hepatocellular apoptosis is a typical characteristic of hepatic disease, and is regulated by the mammalian target of rapamycin (mTOR) signaling pathway. As the main active component of Kudzu (Pueraria lobata) roots, which is frequently used to treat hepatic diseases, Puerarin (Pue) has been reported to alleviate and protect against hepatic injury. However, it is unclear whether Pue can inhibit mTOR signaling to prevent excessive apoptosis in the treatment of hepatic diseases. In the present study, Pue effectively ameliorated pathological injury of the liver, decreased serum enzyme (ALT, AST, γ-GT, AKP, DBIL, and TBIL) levels, regulated the balance between pro-inflammatory (TNF-α, IL-1β, IL-4, IL-6, and TGF-β1) and anti-inflammatory cytokines (IL-10), restored the cell cycle and inhibited hepatocellular apoptosis and caspase-3 expression in rats with liver injury induced by 2-AAF/PH. Pue inhibited p-mTOR, p-AKT and Raptor activity, and increased Rictor expression in the liver tissues of rats with experimental liver injury. These results indicated that Pue effectively regulated the activation of mTOR signaling pathway in the therapeutic and prophylactic process of Pue on experimental liver injury.